Exploring Energy Efficiency and User Attitudes toward Green Energy Implementation in University Buildings - Nurhasan Syah; Syaiful Haq; Faisal Ashar; Yaumal Arbi (International Journal of Environment, Engineering and Education, 2026)
The global push for sustainable development has intensified the need to improve energy efficiency in higher education buildings, particularly in hot–humid tropical climates where cooling demand dominates electricity use. This study examines how occupant perceptions, environmental attitudes, and energy-related behaviors relate to measured building energy performance in a tropical university building, using a convergent parallel mixed-methods design. An ASHRAE Level 1–based energy audit (aligned with Indonesia’s MEMR Regulation No. 13/2012) profiled electricity consumption by end-use systems and was complemented by a 38-item questionnaire and semi-structured interviews with students, lecturers, and administrative staff. The audit estimated total annual electricity consumption of 366,897.7 kWh/year, corresponding to an average Energy Use Intensity (EUI) of 17.34 kWh/m²/month, and associated emissions of 285,108.85 kgCO₂eq. Cooling/HVAC accounted for the largest share of electricity use (≈55%), followed by plug loads/equipment and lighting. Survey results indicated generally high pro-environmental attitudes; however, quantitative associations between aggregated floor-level perceptions/behaviors and electricity use were exploratory, given the limited number of analytic units (four floors/zones). Still, floor-level correlations consistently suggested negative relationships between behavioral variables and energy consumption, with expectations toward green-energy practices showing a particularly strong inverse association (r = –0.968). Qualitative findings highlighted practical operational and behavioral drivers such as temperature setpoints, schedule discipline, and equipment shutdown practices, pointing to actionable opportunities for demand reduction. Overall, the study contributes an integrated audit–behavior perspective to support occupant-centered interventions, green-campus policy alignment, and sustainability-oriented learning activities for long-term low-carbon campus development in hot–humid contexts.